Evaluation of the transmission of Anaplasma marginale by Amblyomma tonelliae - Mazzucco Panizza, Matilde Nahimé; Tarragona, Evelina Luisa; Sebastian, Patrick; Flores, Fernando Sebastian; Mangold, Atilio Jose; Nava, Santiago (Elsevier, 2025)
This study aimed to evaluate A. marginale transstadial (TST) and transovarial transmission (TOT) by Amblyomma tonelliae through vector competence assays and analysis of natural infection in free-living ticks. This three-host tick species was chosen as model because it is a usual parasite of cattle in all their parasitic stages, making them potential vectors through TST or TOT. Experiment 1 was performed to evaluate TST of A. marginale field strains and M1 strain, and the experiment 2 to evaluate TST and TOT of A. marginale S1P strain from an experimentally acutely infected calf. Free-living larvae, nymphs and adults of A. tonelliae were analyzed to evaluate natural infection with A. marginale. One nymph pool of the experiment 2 resulted positive (minimum infection rate of 1.25 %). However, the negative results of both vector competence assays and the molecular analysis of free-living ticks indicate that the transmission of A. marginale by A. tonelliae would not occur. This finding aligns with three of the four existing studies on the TST and TOT of A. marginale by ticks of the Amblyomma genus.